2011
DOI: 10.3201/eid1708.110028
|View full text |Cite
|
Sign up to set email alerts
|

Enterovirus 68 in Children with Acute Respiratory Tract Infections, Osaka, Japan

Abstract: Enterovirus 68 strains were detected in 14 specimens from children with respiratory tract infections and 1 specimen from a child with febrile convulsions during 2010 in Osaka, Japan. These strains had deletions in the 5′ untranslated region and were genetically different from reported strains. This virus is associated with respiratory tract infections in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
84
2
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(95 citation statements)
references
References 12 publications
7
84
2
2
Order By: Relevance
“…We further defined subclades A1, A2, B1, and B2. In line with our subclade definition, subclades A1 and B2 were endemic and found in many countries before the (16,19,30). During the 2014 outbreak, a novel subclade, B1, seems to have rapidly emerged and was dominant during the U.S. outbreak (38,60,61).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…We further defined subclades A1, A2, B1, and B2. In line with our subclade definition, subclades A1 and B2 were endemic and found in many countries before the (16,19,30). During the 2014 outbreak, a novel subclade, B1, seems to have rapidly emerged and was dominant during the U.S. outbreak (38,60,61).…”
Section: Discussionmentioning
confidence: 65%
“…Our phylogenetic analyses are notable in that they suggest a relatively complex molecular evolution of EV-D68 during the 2014 outbreak. Before this outbreak, EV-D68 was rarely reported and was associated with mild respiratory illness, although small outbreaks had been documented since 2005 (15,16,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Previous studies showed that the A, B, and C clades circulated or cocirculated during different time periods in different geographic regions (15,16,18,19,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)59).…”
Section: Discussionmentioning
confidence: 99%
“…Over the past 3 years, outbreaks in Japan, the Philippines, and the Netherlands as well as epidemic clusters in the United Kingdom have implicated HEV-D68 as an emerging respiratory pathogen (2, 4-9). The clinical presentation of HEV-D68 infections during these outbreaks ranged from mild illness to rare severe pneumonia cases requiring admission in intensive care units (2,(4)(5)(6)(7)(8)(9). Among these epidemic strains, novel genetic variants were described (2, 4-8).…”
mentioning
confidence: 99%
“…A global upsurge of EV-D68 infections in patients with respiratory tract infections (RTIs) has been observed in recent years (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). In 2014, a large outbreak of EV-D68 infections occurred in the United States, which raised public health concern owing to severe respiratory illness and neurological complications (22)(23)(24)(25)(26)(27)(28)(29)(30).…”
mentioning
confidence: 99%